Upaya Meningkatkan Motorik Halus Anak melalui Kegiatan 3 M (Mewarnai, Menggambar dan Menempel) di Taman Kanak-Kanak Islam Al Khasanah Gresik - Herawati; Yeni Setiyowati (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2019)
This research is a classroom action research (PTK). The research procedure used includes planning, implementing, observing and reflecting. This study consisted of two cycles, namely cycle I and cycle II. Children's fine motor intelligence varies. In terms of strength and accuracy. this difference is also influenced by the nature of the child and the stimuli it gets. The environment (parents) has a greater influence on children's fine motor intelligence. The environment can increase or decrease the level of intelligence of children, especially in the first few years of life. In cycle 1 the teacher uses 2M activities which are more interesting and can stimulate children in carrying out 3M activities, children are more motivated in carrying out 3 M activities. Many children ask the teacher about the material the teacher delivers. There is a conducive two-way communication in the classroom during the learning process. In cycle 2, the results of the evaluation can be said to be complete with a very good development score (BSB) even though there are some children whose scores are still developing according to expectations (BSH). And from the independent evaluation that I tested, it showed that group B of Al Khasanah Islamic Kindergarten had reached the indicators of developmental achievement in children's fine motor skills through the 3 M.